2019
DOI: 10.1002/lary.28358
|View full text |Cite
|
Sign up to set email alerts
|

Long‐term audiologic outcomes after cochlear implantation for single‐sided deafness

Abstract: Objectives To evaluate the long‐term audiometric outcomes, sound localization abilities, binaural benefits, and tinnitus assessment of subjects with cochlear implant (CI) after a diagnosis of unilateral severe‐to‐profound hearing loss. Method The study group consisted of 60 (mean age 52 years, range 19–84) subjects with profound hearing loss in one ear and normal to near‐normal hearing in the other ear who underwent CI. Data analysis included pre‐ and postoperative Consonant‐Nucleus‐Consonant (CNC) Word scores… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

8
75
1

Year Published

2020
2020
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 55 publications
(84 citation statements)
references
References 31 publications
8
75
1
Order By: Relevance
“…Performance tends to improve with early CI listening experience, but there are discrepancies in the literature about the time course of acclimatization. Some studies observe a plateau in speech recognition by 6 months of CI use 9,12 and others document continued improvement over several years 21–25 . Acclimatization with the CI may be influenced by age at implantation, with older adults needing more listening experience before reaching asymptotic performance as compared to younger adults due to age‐related effects on auditory processing.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Performance tends to improve with early CI listening experience, but there are discrepancies in the literature about the time course of acclimatization. Some studies observe a plateau in speech recognition by 6 months of CI use 9,12 and others document continued improvement over several years 21–25 . Acclimatization with the CI may be influenced by age at implantation, with older adults needing more listening experience before reaching asymptotic performance as compared to younger adults due to age‐related effects on auditory processing.…”
Section: Introductionmentioning
confidence: 99%
“…Some studies observe a plateau in speech recognition by 6 months of CI use 9,12 and others document continued improvement over several years. [21][22][23][24][25] Acclimatization with the CI may be influenced by age at implantation, with older adults needing more listening experience before reaching asymptotic performance as compared to younger adults due to age-related effects on auditory processing. Data on effects of age for asymptotic performance are mixed, as some studies have shown poorer speech recognition for older adults, [26][27][28][29][30][31][32][33] while others indicate no age effect.…”
Section: Introductionmentioning
confidence: 99%
“…Eight large studies of more than 10 patients reported post-lingual adult CI outcomes for 565 individuals and these patients exhibited a mean (SD) post-operative CNC word score of 50.1% (12.5%). [26][27][28][29][30][31][32][33] These outcomes compare similarly to a large systematic review of adult CI outcomes of 2798 patients across 46 studies and showed CNC scores improved from 8.3% (12.4) to 54.0% (22.5) 34 . A one-way ANOVA was conducted to compare mean postoperative CNC WRS between the TMPRSS3 cohort and the eight adult hearing loss studies [66.2% (25.8) vs. 50.1% (12.5)].…”
Section: Resultsmentioning
confidence: 69%
“…40 Regardless of the four poor performers in this study, our post-operative CNC word scores remained comparable to CI outcomes of the general hearing loss population. [26][27][28][29][30][31][32][33] Interestingly, all poor performers carry the p.Ala138Glu mutation, but with different alleles in trans. The p.Ala138Glu variant occurs in the SRCR domain.…”
Section: Discussionmentioning
confidence: 99%
“…Although sparse evidence has demonstrated that CI has "negative effects" on tinnitus [9,10], most studies in this regard have shown that CI is associated with a decrease in the intensity and discomfort caused by tinnitus [8,11]. In fact, in recent years, CI has been used in selected cases of unilateral deafness and asymmetric hearing loss with bothersome tinnitus, with excellent results [12][13][14]. Based on these findings, CI can be a valuable treatment method for patients with tinnitus.…”
Section: Introductionmentioning
confidence: 99%